Molecular self-assembly of a tyroservatide-derived octapeptide and hydroxycamptothecin for enhanced therapeutic efficacy. Issue 9 (2nd March 2021) - Liu, Jing; Wu, Can; Dai, Guoru; Feng, Feng; Chi, Yuquan; Xu, Keming; Zhong, Wenying
Abstract : A pure l -amino acid-based molecular hydrogel was designed through conjugation of an anticancer tripeptide tyroservatide (YSV) with a self-assembling moiety, which enhanced therapeutic efficacy of both YSV and hydroxycamptothecin in vitro and in vivo. Abstract : Tyroservatide (YSV) belongs to a class of bioactive peptides that have drawn considerable attention in the field of drug discovery, yet it displays limited potency and often requires a millimolar concentration to execute its cellular functions. To enhance the potency of the drug through a self-assembling strategy, we designed and synthesized a series of octapeptides through conjugation of YSV with a pentapeptide sequence bearing alternating hydrophobic and hydrophilic amino acids to promote their self-assembling capabilities. Initial screening for hydrogelation gave a novel octapeptide (denoted as 1-YSV hereafter) that was capable of self-assembling under physiological conditions to afford supramolecular nanofibers with enhanced anti-cancer efficacy compared to YSV itself. Interestingly, 1-YSV formed a robust co-assembly with the anticancer drug hydroxycamptothecin (HCPT) to afford 1-YSV/HCPT hydrogel, which not only greatly improved the viscoelastic properties of hydrogels, but also stabilized HCPT in the hydrogel matrix and avoided the agglomeration of drug molecules. Compared to HCPT solution, the hydrogel formulation of 1-YSV/HCPT demonstrated better efficacy against the proliferation of non-small cell lung cancer A549 cells both in vitro and in vivo . Finally, thanks to the pure amino acid-based composition, the 1-YSV/HCPT formulation exhibited excellent biocompatibility, giving a low hemolytic rate to red blood cells, with mild local tissue reactions and negligible systematic toxicities in mice.